2018
DOI: 10.1039/c8ta02115e
|View full text |Cite
|
Sign up to set email alerts
|

Branched comb-shaped poly(arylene ether sulfone)s containing flexible alkyl imidazolium side chains as anion exchange membranes

Abstract: A novel strategy can enhance conductivity and stability of AEMs via the introduction of a branched structure in polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 58 publications
0
61
0
Order By: Relevance
“…However, AAEM conductivity is significantly influenced by hydrophobic-hydrophilic microphase separation, because a well-defined polymer morphology (e.g., bicontinuous hydrophobic-hydrophilic channels) facilitates water/hydroxide transportation in solid-state membranes (14). In previous reports, modifying polymer morphology with multiblock sequences (15)(16)(17)(18), long flexible side chains (18)(19)(20)(21), or microporous structures (22) has improved hydroxide conductivity. For instance, Watanabe and coworkers (15) observed that multiblock poly(arylene ether)s showed significantly higher hydroxide conductivity than their random copolymer analogs [σ (OH − , 60°C) = 126 mS/cm and 35 mS/cm for multiblock and random copolymers, respectively.…”
mentioning
confidence: 99%
“…However, AAEM conductivity is significantly influenced by hydrophobic-hydrophilic microphase separation, because a well-defined polymer morphology (e.g., bicontinuous hydrophobic-hydrophilic channels) facilitates water/hydroxide transportation in solid-state membranes (14). In previous reports, modifying polymer morphology with multiblock sequences (15)(16)(17)(18), long flexible side chains (18)(19)(20)(21), or microporous structures (22) has improved hydroxide conductivity. For instance, Watanabe and coworkers (15) observed that multiblock poly(arylene ether)s showed significantly higher hydroxide conductivity than their random copolymer analogs [σ (OH − , 60°C) = 126 mS/cm and 35 mS/cm for multiblock and random copolymers, respectively.…”
mentioning
confidence: 99%
“…[14][15][16] Recently, our group reported a set of highly branched sulfonated poly(arylene ether) membranes, [16][17][18] and one of the branched membranes, poly(fluorenyl ether ketone sulfone)s (BSPFEKS), displayed the proton conductivity of 0.42 S cm −1 and oxidative stability of 327 minutes. 16 Branched structure imparts high free volume in the polymer matrix, 19 thus decreasing its methanol barrier ability and mechanical strength. Herein, we synthesized the highly branched partially fluorinated sulfonated poly(ether ketone sulfone) by changing the bisphenol monomer.…”
Section: Discussionmentioning
confidence: 99%
“…Xu group reported AEMs based on the hyperbranched polymer structures containing QA groups, which processed high ionic conductivity and prolonged stability under alkaline conditions . In addition, polymer backbones containing branched side chains with multiple cation groups are also considered as an effective approach to boosting ion conducting for it constructs inter‐connected ion conducting channels . Our group has developed branched comb‐shaped copolymers as AEMs, which exhibited high ionic conductivity and robust alkaline stability .…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Our group has developed branched comb-shaped copolymers as AEMs, which exhibited high ionic conductivity and robust alkaline stability. 32 However, introducing branched structures may result in a larger distance between molecular chains, thus deteriorated the mechanical strength of the membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation